2020
DOI: 10.3389/fpsyg.2020.02235
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Psychosocial Well-Being of Migrants in Spain: The Moderating Role of Sense of Community

Abstract: The discrimination migrants perceive during their adaptation process is one of the main sources of stress and it affects their well-being, health and integration severely. The present study analyses how the sense of community (SOC) can have a protective effect against the perception of discrimination and its negative consequences by verifying the following theoretical model: discrimination predicts three indicators of psychosocial well-being (psychological distress, satisfaction with life and feelings of socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 142 publications
2
14
0
1
Order By: Relevance
“…In addition, each community should make full use of its resources, such as working with social organizations, increasing community activities, improving community conflict and dispute mediation mechanisms, etc. This would promote the acculturation and identity integration of migrant workers, help migrant workers and local residents form good social relations, and enhance the social trust, security, and happiness of migrant workers ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, each community should make full use of its resources, such as working with social organizations, increasing community activities, improving community conflict and dispute mediation mechanisms, etc. This would promote the acculturation and identity integration of migrant workers, help migrant workers and local residents form good social relations, and enhance the social trust, security, and happiness of migrant workers ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research on collective action provides an explanatory model that might be a useful starting point in exploring what enables empowerment. García-Cid et al (2020), for example, found that sense of community (SOC) can moderate negative impacts of discrimination and that interventions in immigrant communities that increase positive encounters with the receiving community and prioritize SOC can forge collective action. A focus on the collective, macro community is supported by Klandermans et al’s (2008) study of Muslim immigrants in the Netherlands and New York City, in which they found no substantial differences between immigrants and receiving community members in the psychosocial mechanisms that led to collective action.…”
Section: Discussionmentioning
confidence: 99%
“…Third, community resources should be put into full use. For instance, more community activities can be organized and the mediation mechanism for community conflicts and disputes can be improved to promote the social adaptation and cultural integration of young migrants, helping them form good social relations with local residents and enhance their social trust, sense of security and happiness ( García-Cid et al, 2020 ). Moreover, in the case of routine management for the new crown epidemic, professional psychological counseling can be offered to the young migrants in the community to alleviate the psychological impact of the epidemic on them, adding to the all-around support for their social integration ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%